"And Also Because I have Not Dug the Field of My Heart": A Contribution to the Question of the Thematisation of the Self among Czech Secret Non-Catholics in the 18th Century - Horský, Jan (Dějiny – teorie – kritika, 2024)
This article carries on from the analysis of the "religious culture" of Würtemberg Lutheran pietism offered by Ulrike Gleixner, and is based on the theoretical concepts of culture used in Anthropological History and New Cultural History. Gleixner´s study shows the central importance in religious culture that "rebirth in the Holy Spirit" had for the thematisation of the self among 18th-century pietists. The question is whether we might find similar cultural categories serving as instruments of thematisation of the self in the "religious culture" of 18th-century Czech non-Catholics, who were partially influenced by Lutheran pietism. The article is focused on the analysis of a number of selected sources (especially the letters of the Czech serf Matěj Němeček of 1732, in which he gives reasons for his departure into Protestant exile), and it considers how the categories of "rebirth", the "heart" and "conscience" are treated. While Němeček does not speak directly of "rebirth", in the way that he describes himself we can find equivalents to rebirth that in a certain sense show a sectarian character (he regards a secular promise as sinful, the religious transformation of the self needs to be affirmed by emigration to a non-Catholic country, and this is understood as a work of salvation).